2013
DOI: 10.1590/s1519-69842013000200016
|View full text |Cite
|
Sign up to set email alerts
|

Benthic insects of the El Tala River (Catamarca, Argentina): longitudinal variation of their structure and the use of insects to assess water quality

Abstract: The aim of this work was to determine the structure of the benthic entomofauna and its variation along the El Tala River (Catamarca, Argentina). Five sampling stations were established, considering the location of nearby housing with respect to the watercourse. The following variables were determined in situ: altitude, latitude and longitude, bedstream width, river depth, river-current speed, water and air temperatures. Benthic insects were collected with a square parcel sampler of 0.09-m 2 area and 300-µm net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…The results obtained in the present study, were collected in mountain zone, three stations in zone with native forest without human intervention, and two stations in a zone with human intervention, revealing the marked differences in benthic fauna, these results were similar to descriptions for mountain rivers in Catamarca, in northern Argentinean Andes (Colla et al, 2013) and Rio Grande do Sul in Brazil (Bertaso et al, 2015). The exposed results are different to other descriptions of Chilean rivers, because, these studies were conducted in rivers bed with a marked human intervention gradient without include mountain zones where is located the riverbed origin (Figueroa et al, 2003(Figueroa et al, , 2007, perhaps, the similarities would be with studies in coastal mountain rivers with altered basins due agriculture and forestry activities between 38-39°S (Fierro et al, 2012(Fierro et al, , 2015.…”
Section: Discussionsupporting
confidence: 87%
“…The results obtained in the present study, were collected in mountain zone, three stations in zone with native forest without human intervention, and two stations in a zone with human intervention, revealing the marked differences in benthic fauna, these results were similar to descriptions for mountain rivers in Catamarca, in northern Argentinean Andes (Colla et al, 2013) and Rio Grande do Sul in Brazil (Bertaso et al, 2015). The exposed results are different to other descriptions of Chilean rivers, because, these studies were conducted in rivers bed with a marked human intervention gradient without include mountain zones where is located the riverbed origin (Figueroa et al, 2003(Figueroa et al, , 2007, perhaps, the similarities would be with studies in coastal mountain rivers with altered basins due agriculture and forestry activities between 38-39°S (Fierro et al, 2012(Fierro et al, , 2015.…”
Section: Discussionsupporting
confidence: 87%
“…To note, the cosmopolitan family Chironomidae (Andersen et al, 2000;Saether and Ekrem, 2003) showed the highest frequency in the study area, consistent with previous studies of arid and semi-arid environments in South America (Scheibler, 2008;Colla et al, 2013;Zelarayán and Salas, 2014;Ferru and Fierro, 2015;Domínguez et al, 2020).…”
Section: Key Findings In Arid and Semi-arid Ecosystems Of Perusupporting
confidence: 88%
“…The electrical conductivity values ' of the sites sampled in the Río Grande basin located in the Puna and the Monte were higher than those reported by Nieto et al (2016), Hankel et al (2018 and Pero et al (2019) for different rivers of arid zones of northwestern Argentina. The other sites located in Yungas showed values ' of EC and TDS similar to those reported previously (Fernández et al 2002;Colla et al 2013;Zelarayán Medina and Salas 2014;Pero et al 2019), while the main channel showed somewhat higher values.…”
Section: D���������supporting
confidence: 88%